Appropriate technology adaptation to mitigate community transmission of SARS CoV2 virus in resourced challenged Bhutan and Bangladesh - Khandaker, Nadim Reza (Universitas Nahdlatul Ulama Surabaya, 2021)
The SARS CoV2 pandemic has a tremendous impact on both developed and developing countries. To mitigate against community transmission of SARS CoV2 in Southern Bhutan and Central Bangladesh, the development and application of appropriate technologies was undertaken. As an appropriate mitigation, hand washing station was constructed by a simple system. The system was operated using a foot pedal to limit cross contamination by direct hand contact, hand sanitizer utilization and disinfection application in Central Bangladesh. The study highlighted a local innovation in constrained environments to provide public health solutions for preventing the spread of SARS CoV2. The innovation and mitigation measures can be replicated in other resource challenged regions of the world as mitigations steps to limit community transmission of SARS CoV2.